Changes in trends and impact of testing for influenza in infants with fever <90 days of age. Issue 12 (20th December 2017) - Kim, Suji; Moon, Hye Min; Lee, Joon Kee; Rhie, Kyuyol; Yoon, Ki Wook; Choi, Eun Hwa; Lee, Hoan Jong; Lee, Hyunju
Abstract: Background: Infants aged <90 days who present with fever commonly undergo various invasive procedures due to the risk of bacterial infection in this age group. A great proportion of cases, however, are due to viral infection, including influenza. The aim of this study was therefore to assess the impact of influenza testing in infants <90 days with fever, as well as analyze the subject characteristics to identify which infants should be considered for such testing. Methods: Clinical characteristics and trends in influenza virus testing and treatment were analyzed among febrile infants <90 days who presented to the emergency room and were diagnosed with influenza during 2005–2015. Results: Among 5, 347 febrile infants aged <90 days, 963 (18%) underwent influenza virus test. A total of 114 (11.8%) were diagnosed with influenza. The positivity rate reached 67% of febrile infants during epidemics. Of them, 83 had a history of family contact. While more than half presented with upper respiratory symptoms, 34% had only fever without respiratory symptoms. A decrease in antibiotic use and admission rates during the study period among infants diagnosed with influenza was seen ( P for trend <0.05). Conclusions: During the influenza epidemic season, diagnostic tests for influenza based on a detailed contact history are necessary in assessing the cause of fever. Targeted testing for influenza may lead to a decrease in antibiotic use and admission rates in young infants.